Exercise antagonizes cadmium-caused liver and intestinal injury in mice via Nrf2 and TLR2/NF-κB signalling pathway - Ding Zhang; Jiayi Liu; Jingru Liu; Maryam Fatima; Lu Yang; Yingze Qin; Wei Li; Zilong Sun; Bo Yang (Ecotoxicology and Environmental Safety)
Cadmium (Cd) causes a health risk to humans and animals. Exercise can prevent and treat a variety of diseases, but the effect and mechanism of exercise on cadmium poisoning are still unclear. The present research aims to investigate the antagonistic impacts of exercise on enterotoxicity and hepatotoxicity caused by Cd. The results indicated that exercise, both before and during Cd exposure, can reduce Cd caused pathological damages in the liver and duodenum of mice, suppressing the expression levels of the IL-1β, IL-6 and TNF-α genes. In mice exposed to Cd, exercise significantly decreased blood ALT and AST levels, alleviating oxidative stress in the liver by reducing MDA synthesis and enhancing SOD and GSH-PX activities. Exercise inhibited nuclear damage and hepatocyte apoptosis caused by Cd by increasing Bcl-2 protein expression and preventing the release of pro-apoptotic proteins such as caspase-3, Cytc, Bax, caspase-8and cleaved-caspase-3. Exercise before or during Cd exposure can increase the protein and gene expression of HO-1, NQO-1 and Nrf2 in the liver of mice exposed to Cd. These findings suggested that the Nrf2 signaling pathway may have contributed to the exercise-induced partial attenuation of Cd-induced hepatic injury. Exercise also promoted the expression of the occludin gene in the duodenum of Cd-exposed mice, decreasing the structural damage and inflammatory cell infiltration induced by Cd. NF-κB and TLR2 protein expression levels were elevated in mice exposed to Cd. However, exercise mitigated the increase in NF-κB and TLR2 expression in the duodenum of Cd-intoxicated mice, suggesting that the protective effects of exercise on the intestinal tract in Cd-exposed mice may be mediated through modulation of the NF-κB/TLR2 signaling pathway. In conclusion, this study elucidated the protective effects of exercise against Cd-induced hepatotoxicity and intestinal injury in mice. The protective mechanisms of exercise on Cd-exposed liver and intestinal tract were partially realized through the regulation of Nrf2 and NF-κB/TLR2 signaling pathways.